The chequered history of music education in Nigeria (2015)
Musical arts education has remained a veritable and enculturative medium in African society. Its inclusion in Nigeria’s school curriculum by the policy makers is a testimony of the recognition of its potential for optimal realization and utilization of human resources; not only in terms of norms, customs and folklore of the people in general but also as an important tool for national development. This paper attempts a chequered history of music education in Nigeria from the pre-colonial era to date: It also appraises government's recent negative policy in further annihilating music as a subject from the nation’s school curriculum and suggests strategies by which pro-active musical arts educators could effectively the present cultural and creative arts programme in order to bring about the desired results.